2018
DOI: 10.5210/fm.v23i10.9435
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing materiality from print to screen reading

Abstract: The shift from print to screen has bodily effects on how we read. We distinguish two dimensions of embodied reading: the spatio-temporal and the imaginary. The former relates to what the body does during the act of reading and the latter relates to the role of the body in the imagined scenarios we create from what we read. At the level of neurons, these two dimensions are related to how we make sense of the world. From this perspective, we explain how the bodily activity of reading changes from print to screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Thus, "[t]he unfolding meaning attribution to the text occurs without much material anchoring." [37]. And the same might apply to audiobooks as well.…”
Section: Implication #4: In Order To Facilitate Individuals' Readingmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, "[t]he unfolding meaning attribution to the text occurs without much material anchoring." [37]. And the same might apply to audiobooks as well.…”
Section: Implication #4: In Order To Facilitate Individuals' Readingmentioning
confidence: 93%
“…Though the differently materialized forms of books already provide various possibilities for different bodily or mental needs and preferences, we have not yet developed sufficient, satisfying options. For instance, Schilhab et al [37] explain how…”
Section: Implication #4: In Order To Facilitate Individuals' Readingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of brain functions have shown that the same areas of the brain that store sensory input and control motor output are used when processing abstract thoughts, such as space, distance and love (Groh, 2014). For example, from their perspective within the reading sciences, Schilhab et al (2018) have documented how our brain uses what they refer to as 'material anchors' in memory, when discussing how we understand and read a written text: '[t]he reading activity 'speaks' to us at several levels: the sensory, perceptual, motor, conceptual and affective level. All of these levels participate in forming the so-called neural correlate, which is the bundle of neurons active during the reading' (3rd paragraph).…”
Section: Introductionmentioning
confidence: 99%
“…4.While this was a practical solution to increase the number of participants, it must be kept in mind that some studies suggest that the use of two different reading formats (hard copy and electronic) may encourage differences in attentional engagement/comprehension (see, for example, Mangen et al, 2013; Schilhab et al, 2018). …”
mentioning
confidence: 99%